TEACHING COMPOSITION IN A FLIPPED CLASSROOM. (October 2022) - Iddon, Martin; McLaughlin, Scott
Abstract : In 2019 the present authors, along with our colleague Mic Spencer, began work on a project funded by the Leeds Institute for Teaching Excellence, designed to look at the ways in which we taught composition at the University of Leeds and how we might change them. Mic has focused on postgraduate teaching, and we have considered the earliest parts of the undergraduate curriculum, particularly the first two years of study, when the largest numbers of students with the least experience of the study of composition at tertiary level might be in a classroom (50 or so, in our case).